FACTORS INFLUENCING VOCATIONAL SCHOOL STUDENTS’ BEHAVIOUR IN USING GENERATIVE AI: PERSPECTIVES FROM THE THEORY OF PLANNED BEHAVIOUR AND AI LITERACY - Lisya Dini Saputri; Jaka Nugraha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyse the factors influencing the behaviour of vocational high school (SMK) students in using Generative Artificial Intelligence (GAI) from the perspective of the Theory of Planned Behaviour (TPB) and AI literacy. The background to this study is based on the increasing use of AI technology in education, which has not yet been fully matched by an understanding of AI literacy and the ethics of its use. This study employs a quantitative approach with an explanatory research design using a survey method. Data were collected via a Likert-scale questionnaire from 193 students at SMKN 1 Magetan in the Office Management department for the 2024/2025 academic year. Data analysis was conducted using Structural Equation Modelling Generalised Structural Component Analysis (SEM-GSCA) via the GSCA-Pro application. The results indicate that AI literacy has a significant influence on students’ attitudes, and these attitudes have a positive influence on behavioural intention regarding the use of Generative AI. These findings suggest that the higher the students’ level of AI literacy, the more positive their attitudes and intentions are towards utilising AI technology to support the learning process. The conclusion of this study indicates that strengthening AI literacy is necessary to foster responsible AI usage behaviour within the educational environment. ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi perilaku siswa Sekolah Menengah Kejuruan (SMK) dalam menggunakan Generative Artificial Intelligence (GAI) berdasarkan perspektif Theory of Planned Behavior (TPB) dan literasi AI. Penelitian ini dilatarbelakangi oleh semakin meningkatnya pemanfaatan teknologi kecerdasan buatan dalam dunia pendidikan yang belum sepenuhnya diimbangi dengan pemahaman mengenai literasi AI serta etika penggunaannya. Penelitian menggunakan pendekatan kuantitatif dengan desain explanatory research melalui metode survei. Data dikumpulkan menggunakan kuesioner skala Likert terhadap 193 siswa Program Keahlian Manajemen Perkantoran di SMKN 1 Magetan Tahun Ajaran 2024/2025. Analisis data dilakukan menggunakan Structural Equation Modeling–Generalized Structured Component Analysis (SEM-GSCA) melalui aplikasi GSCA-Pro. Hasil penelitian menunjukkan bahwa literasi AI berpengaruh signifikan terhadap sikap siswa, dan sikap tersebut berpengaruh positif terhadap niat berperilaku dalam menggunakan Generative AI. Temuan ini mengindikasikan bahwa semakin tinggi tingkat literasi AI yang dimiliki siswa, semakin positif pula sikap dan niat mereka dalam memanfaatkan teknologi AI untuk mendukung proses pembelajaran. Penelitian ini menyimpulkan bahwa penguatan literasi AI perlu dilakukan untuk membentuk perilaku penggunaan AI yang bertanggung jawab di lingkungan pendidikan.